Lung ultrasound score as an indicator of dynamic lung compliance during veno-venous extra-corporeal membrane oxygenation. Issue 3 (March 2021) - Ntoumenopoulos, George; Buscher, Hergen; Scott, Sean
Decisions on weaning from veno-venous extra-corporeal membrane oxygenation (VV-ECMO) requires the ability to maintain adequate gas exchange and work of breathing with reductions in ECMO pump flow and fresh gas flow. Testing of the readiness to wean the patient from ECMO however may vary dependent upon local protocols and clinical judgment. This study sought to validate the use of the LUS-score during VV-ECMO against the changes in chest x-ray infiltrates, dynamic lung compliance (CLdyn) and VV-ECMO settings (as standard measures of native lung function and the level of ECMO support) during the ECMO cycle. This prospective cohort study of 10 patients on VV-ECMO compared the LUS score (range 0–36) within 48-h, day 5 and day 10 of commencement of ECMO (or on the day of ECMO decannulation) to dynamic lung compliance, Murray Lung Injury Score and ECMO settings. Seven Male and three Female patients were included (average age 37 years (SD 14.8) and weight 71 Kg (SD 16.9). Median (IQR) duration of ECMO, ICU and hospital length of stay was 7.5 days (5.2–19.0), 12.5 days (8.5–22.7), 19.0 days (12.1– 36.1), respectively. There was a strong negative association between LUS-score and dynamic lung compliance (rs (33) = –0.66, p < .001) providing some validation on the use of the LUS score as a potential surrogate measure of lung aeration and lung mechanics during VV-ECMO weaning.